2008
DOI: 10.1593/neo.08388
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Heterogeneity in Blood Supply in Human Tumor Xenografts

Abstract: Temporal heterogeneities in tumor blood supply were studied by using a recently developed first-pass imaging technique. First-pass imaging movies of A-07-GFP human tumor xenografts growing in window chambers were recorded at a frame rate of approximately 9 fps and a spatial resolution of 10.8 x 10.8 microm(2) after a bolus of 155-kDa tetramethylrhodamine isothiocyanate-labeled dextran had been administered intravenously. Each tumor was subjected to imaging thrice, with 20 minutes between each repetition. Highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…49 Research to characterize acute fluctuations in tumor microvessel oxygenation and perfusion requires advanced imaging techniques with microvessel resolution. 50 Spectral imaging of tumor microvessel oxygenation may be a useful tool in this effort. We previously showed that spectral imaging could be used to measure acute fluctuations in tumor microvessel oxygenation.…”
Section: Tumor Microvascular Acute Oxygenation Fluctuationsmentioning
confidence: 99%
“…49 Research to characterize acute fluctuations in tumor microvessel oxygenation and perfusion requires advanced imaging techniques with microvessel resolution. 50 Spectral imaging of tumor microvessel oxygenation may be a useful tool in this effort. We previously showed that spectral imaging could be used to measure acute fluctuations in tumor microvessel oxygenation.…”
Section: Tumor Microvascular Acute Oxygenation Fluctuationsmentioning
confidence: 99%
“…This was a widely observed phenomenon in both transplanted and spontaneously arising tumours. [48][49][50] It was subsequently shown that tumours usually contain regions subject to fluctuating blood flow, 51,52 leading to the concept that tumour cells may be exposed to either chronic or acute (cycling) hypoxic environments and that observed reoxygenation could be partially explained by such cycling hypoxia. Chronic hypoxia is largely thought to occur as a result of oxygen diffusion limitations, but potentially, it may also result from the presence of unusually long vessels or slow blood flow when the oxygen capacity of the blood may be exhausted along the length of the vessel.…”
Section: Role Of Hypoxiamentioning
confidence: 99%
“…Prolonged or chronic hypoxia is regarded as "diffusion-limited" hypoxia in which tumor cells are located far away from the vascular supply, whereas acute hypoxia in tumors is considered as "perfusionlimited" hypoxia, in which tumor oxygenation fluctuates over time [54][55][56]. Hypoxia in tumors is a well-established poor prognostic indicator as it promotes aggressive transformation of tumor cells leading to enhanced metastatic potential [57][58][59], and it is well recognized that hypoxic tumor cells are more radioresistant than nonhypoxic cells [60].…”
Section: Hypoxic Microenvironment/nichementioning
confidence: 99%